PENGEMBANGAN BUKU PANDUAN MENENTUKAN PIKIRAN POKOK PARAGRAF MENGGUNAKAN MODEL SKRAMBEL (Universitas Negeri Semarang, 2017)
The research of development guidebook to determine main idea of the paragraph using scramble model aimed to knowing the character, validity, effectiveness, and practicality of the guidebook to determine main idea of the paragraph using scramble model. This research type is research and development (R & D), using research method from Sugiyono. The results of this research showed that: (1) The developed guidebook contained a typical component of the scramble model on the exercise and evaluation questions part of the guidebook; (2) Guidebook is valid by validation from material and media experts. Obtained percentage and criteria eligibility of content 95% (very valid), eligibility of presentment 100% (very valid), scramble scoring 100% (very valid), eligibility of graphic 89.33% (very valid), and eligibility of language 90% (very valid); (3) The guidebook has an effect at the cognitive learning outcomes showed by the significance value of t test is 0.000 <0,05 and score of the gain test is 0.43 with medium criteria; (4) The percentage of student’s responses after using guidebook in classical is 89.42% with very positive criteria, the percentage of teacher response is 95% with very positive criteria. The conclusions of this research are developed guidebook characterized by scramble model, guidebook is valid, effective can improve student learning outcomes and practical for learning Indonesian Language.